Isolated Left Main Coronary Artery Stenosis after Thoracic Radiation Therapy: To Operate or Not to Operate - Osama Alsara; Ahmad Alsarah; Jagadeesh K. Kalavakunta; Heather Laird-Fick; George S. Abela (Case Reports in Medicine)
Radiation therapy of neoplasms involving the chest or mediastinum results in a wide spectrum of cardiac complications including coronary artery disease, which can present in patients with few or no traditional cardiac risk factors. We report a case of radiation induced coronary artery disease in a 60-year-old female with a history of stage IIIA nonsmall cell lung carcinoma which was diagnosed eight years earlier and treated with chemotherapy and radiotherapy. She presented to the hospital with atypical chest pain that had occurred intermittently over the preceding week. Her initial electrocardiogram and cardiac enzymes were within normal limits. However, following an indeterminate exercise nuclear stress test, she developed chest pain and elevated cardiac enzymes. Coronary angiography demonstrated 90% stenosis of the left main coronary artery ostium, without any evidence of atherosclerotic disease or stenosis in other coronary arteries. She underwent surgical revascularization, which revealed dense adhesions surrounding the heart. During surgery, she developed severe bleeding and died. Coronary artery disease can present within years of radiation exposure, and ostial lesions are typical. Treatment is often challenging because of the effects of radiation on other tissues and the risks of revascularization procedures. Therefore, a multidisciplinary team approach should be considered.